“Estrangeirismo” and flexibility: intercultural learning in Brazilian MNCs - Bartel-Radic, Anne (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2013)
How do Multinational Companies (MNC) learn to adapt to foreign markets and cultural differences ? We examine seven qualitative case studies of Brazilian MNCs which show that international experience and intercultural interaction, supported by geocentric international human resource strategies, are key factors in the organizational development of intercultural competence. Brazil appears to be a particularly interesting case, as certain characteristics of Brazilian culture, such as “estrangeirismo” and flexibility, seem to foster the development of intercultural competence.